Children in Conflict with The Law: Understanding the Risk and Protective Factors and its Implications for Prevention Efforts - Rahmat Syarif Hidayat; Nunung Nurwati; Binahayati Rusyidi; Kanya Eka Santi (Asian Social Work Journal, 2022)
Data and facts from the media show that the problem of children who conflict with the law is still a daily consumption. This phenomenon of child problems requires serious attention and handling from various parties. The impact of the behavior of children in conflict with the law is not only on the victim but also on the perpetrator himself, the family, and society in general. This article is directed to answer the question of how the risk, protector, and implications for child prevention efforts conflict with the law. This study is based on the study of literature from the perspective of social construction which views that conflict with the law as the reality of the interaction of the individual child and his environment. Social construction recognizes that psychological and sociological aspects work together in combination and this helps create and shape individual realities. The everyday reality experienced by the individual is a reality that affects the response of his/her attitudes and behavior. Individual behavior is a picture of the behavior of people who interact with them. Children generally grow up in four contexts where they interact with others for a long time, namely family, school, peers, and community environments. The four environmental contexts are not only risk factors but become protective factors for the occurrence of child behavior in conflict with the law. References to this paper are sourced from books, journals, and other reliable sources and have an element of novelty both from within Indonesia and from abroad. This paper is intended to be a concern and awareness for various parties so that finally the prevention efforts carried out have the maximum impact and cases of children who conflict with the law are not repeated.